Expert Consensus on Formatted and Intelligent Documentation of Geriatric Rehabilitation Inpatient Medical Records - Geriatric Rehabilitation Committee of Chinese Rehabilitation Medical Association (康复学报)
Standardized and intelligent documentation of geriatric rehabilitation inpatient medical records is crucial for ensuring healthcare quality, enhancing the clinical efficiency of rehabilitation physicians, and optimizing the medical insurance payment management. Based on the core framework of the ‘Expert Consensus on Key Elements of Medical Record Documentation for Elderly Rehabilitation Inpatients', our group developed an intelligent-assisted tool for the documentation of medical record. The tool integrates predefined standardized templates, interactive data-entry components, and a rule engine-driven intelligent assistance module to help rehabilitation practitioners generate inpatient records efficiently. The key elements of standardized documentation for elderly rehabilitation inpatient records mainly include standardized chief complaints, structured prompts for present illness, quantitative specialized physical examinations, disease/functional diagnoses, and rehabilitation treatment plans. This consensus emphasizes a function-oriented assessment framework and establishes a diagnostic classification system for the medical record homepage that aligns with current medical insurance payment standards. By implementing standardized management throughout the entire process from medical record documentation to rehabilitation treatment, this consensus provides a reference for geriatric rehabilitation inpatient medical records across all levels of healthcare institutions in China.